EFFECTIVE APPROACHES FOR TEACHING ENGLISH FOR ESP - Aliyevna, Yuldasheva Dilorom (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
This article demonstrates some main ways and methods for teaching English for ESP students. Also, some methods and ways of having interactive and interesting during the lesson as well as some examples of the methods and their role in teaching are discussed in the following article.